Research in Education - Chacón Rojas, Gilda (1990)
The investigation in the Education, since in any discipline, must have very clear which are the aspects in which it is going to be emphasized the frame of the general topic. For this it is important to establish which is the approach that wants to give and then to define what type of bibliographical material is the one that one adapts more him.